2015
DOI: 10.1007/s10142-015-0468-6
|View full text |Cite
|
Sign up to set email alerts
|

Jasmonic acid involves in grape fruit ripening and resistant against Botrytis cinerea

Abstract: Fruit ripening is a complex process that is regulated by a signal network. Whereas the regulatory mechanism of abscisic acid has been studied extensively in non-climacteric fruit, little is know about other signaling pathways involved in this process. In this study, we performed that plant hormone jasmonic acid plays an important role in grape fruit coloring and softening by increasing the transcription levels of several ripening-related genes, such as the color-related genes PAL1, DFR, CHI, F3H, GST, CHS, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
63
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(70 citation statements)
references
References 84 publications
7
63
0
Order By: Relevance
“…In our results, RR treatment decreased the transcript abundance of brassinosteroid-6-oxidase 2 and this was correlated with an increase in the brassinosteroid contents. In grape berries, jasmonic acid contents increased continuously until 9 weeks post-flowering and then sharply declined to a low level, consistent with the changes of its biosynthesis-related genes [46]. From our results, it can be inferred that RR treatment can increase the jasmonic acid contents during grape berries development and ripening.…”
Section: Discussionsupporting
confidence: 82%
“…In our results, RR treatment decreased the transcript abundance of brassinosteroid-6-oxidase 2 and this was correlated with an increase in the brassinosteroid contents. In grape berries, jasmonic acid contents increased continuously until 9 weeks post-flowering and then sharply declined to a low level, consistent with the changes of its biosynthesis-related genes [46]. From our results, it can be inferred that RR treatment can increase the jasmonic acid contents during grape berries development and ripening.…”
Section: Discussionsupporting
confidence: 82%
“…Similar results have been reported in peach [26] and grape [46]. In peach, the peak of ethylene release occurs earlier after MeJA treatment.…”
Section: Discussionsupporting
confidence: 89%
“…In peach, the peak of ethylene release occurs earlier after MeJA treatment. Jia et al [46] revealed that JA plays an important role in grapefruit softening by increasing the transcription levels of several ripening-related genes. In the present study, treatment with MeJA resulted in an obvious increase in DkLOX3 expression during persimmon fruit ripening (Figure 5B).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was recently demonstrated that JA plays an important role in grape berry coloring and softening by inducing the transcription of several ripening-related genes, such as phenylpropanoid genes, cell wall metabolism-related genes and genes involved in aroma accumulation (Jia et al, 2016). Consistently, we observed that at Stage 2 and Stage 3 several terpenoid synthase genes (e.g., one geraniol 10-hydroxylase and several different terpene synthases), involved in berry aromatic compounds accumulation, was found commonly upregulated by PFD in Bologna and Ancona in 2012, together with jasmonate O -methyltransferase.…”
Section: Discussionmentioning
confidence: 99%